PENGGUNAAN ALAT PERAGA PAPAN GEOMETRI DENGAN METODE PENEMUAN TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI LUAS BELAH KETUPAT DAN LAYANG-LAYANG - Kantohe, Elisabeth (Jurnal Elektronik Pendidikan Matematika Tadulako, 2013)
Abstract: Target of this research is to obtain;get deskripsi usage of appliance physic of geometry board with invention method guided able to improve result learn class student of VII SMP Negeri 19 Palu at wide items of rhombus and kite. Research type is research of class action. The research plan refer at model of Kemmis and Mc. Taggart. Pursuant the result of research, that study using visual appliance of geometry board with invention method guided to make active student in study and also make student find by self wide formula of rhombus and kite, so that student can keep in view the formula.